Foreign Direct Investment in Nepal: A Study on its Impact on Employment - Kharel, Khom Raj (Interdisciplinary Journal of Management and Social Sciences, 2020)
Foreign direct investment (FDI) plays an important role boosting industrial development and promotion of manufactured exports for the developing countries. FDI helps mobilization of capital, human and natural resources of the country, which in turn supports to make the economy dynamic and competitive. FDI is an important source of inflow of capital for economic growth and employment generation in developing countries. It also provides a package which constitutes new technologies and management techniques, financial and market access for the production and movement of goods and services. Though, attracting foreign direct investment has become the major challenges for host countries as it faces the challenges of identifying the major factors that motivate and affect the FDI location decision. That’s why Nepal is at a point wherefrom it can excel for economic goals via FDI. Foreign investment is critical to enhance the transfer of capital, modern technology, management and technical skill, increase culture. This article attempts to explore the growth and trends as well as condition of FDI. The results show a significant association between the changes in FDI on Employment. The finding of multiple regression analysis between FDI and employment indicates that FDI is a significant predictor of employment.